2017
DOI: 10.1093/ndt/gfx277
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk in patients on hemodiafiltration versus hemodialysis: a ‘real-world’ comparison from the DOPPS

Abstract: BackgroundWith its convective component, hemodiafiltration (HDF) provides better middle molecule clearance compared with hemodialysis (HD) and is postulated to improve survival. A previous analysis of Dialysis Outcomes and Practice Patterns Study (DOPPS) data in 1998–2001 found lower mortality rates for high replacement fluid volume HDF versus HD. Randomized controlled trials have not shown uniform survival advantage for HDF; in secondary (non-randomized) analyses, better outcomes were observed in patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 24 publications
(33 reference statements)
1
69
0
Order By: Relevance
“…The Cochrane Review undertaken by Nistor et al (2015) supports this conclusion and could only find statistically significant evidence for patient improvement with respect to reduced mortality from CVD for patients receiving HDF. These findings have been replicated in the more recent large scale cohort study of DOPPS data completed by Locatelli et al (2017).…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…The Cochrane Review undertaken by Nistor et al (2015) supports this conclusion and could only find statistically significant evidence for patient improvement with respect to reduced mortality from CVD for patients receiving HDF. These findings have been replicated in the more recent large scale cohort study of DOPPS data completed by Locatelli et al (2017).…”
Section: Resultsmentioning
confidence: 61%
“…More recent analysis of DOPPS data by Locatelli et al (2017) has also concluded that HDF could not demonstrate improved patient survival over conventional HD therapy. This was a cohort study of patients aged 18 or over and receiving in-centre HD or HDF.…”
Section: Hdf Evidence Basementioning
confidence: 99%
See 3 more Smart Citations